SIFAT MEKANIK ALUMINIUM 5052 PADA PENGELASAN MIG DENGAN VARIASI UKURAN BACKING CERAMIC - Evhardi Danang Susatyo; Nur Yanu Nugroho (JURNAL JALASENA, 2023)
In the modern world, the use of aluminum in the field of construction has often been encountered, including in the field of ship construction. When the welding process is on large construction structures such as ships, it sometimes requires a back and forth welding process, therefore a media in the form of a ceramic backing is used as a support and prints the results of the weld for better results. Using this ceramic backing can save budget and can speed up the work process. From the discussion above, it is necessary to conduct research on the effect of ceramic backing diameter on Aluminum 5052 welding using the MIG (Metal Inert Gas) welding process with a diameter ratio of 6mm, 12mm and 14mm, which aims to compare the results of welding on tensile strength, bending strength, macrographic observation, and penetrant testing. From the results of the Tensile test, the highest average value was obtained for the 6mm Ceramic Backing variation of 64.94 Mpa. From the results of the bending test the best results were obtained on the 14mm Ceramic Backing variation with the minimum crack results of 0.4mm. From the results of the penetrant test, the best results were found in the 12mm Ceramic Backing variation, only 1 rounded of 0.6mm was found. From the results of the macrographic test the best results were found in the 12mm Ceramic Backing variation because there were minimal defects found in the welds.